Products Evaluation of Environmental Education Curriculum/Program Implementation in the University of Calabar, Nigeria - Eneji, Chris-Valentine Ogar; Otu, Benard Diwa; Ita, Caroline I; Onnoghen, Usang Nkanu; Ojong, Aganyi Asu; Esuabana, Stella Bassey; Petters, Janets Sunday; Arop, Lucy Obil; Essien, Cecilia Kori; Omini, Ettah Ettah; Monity, Monity Flora Michael (International Journal of Learning, Teaching and Educational Research, 2023)
This study evaluates the implementation of the environmental education curriculum in the Department of Environmental Education, University of Calabar, Nigeria. Using the expost facto research design, nine objectives were pursued. These include: 6 strategic objectives, the curriculum content, career prospects of graduates, and lecturer’s pedagogic knowledge and problems militating against the effective implementation of Environmental Education (E.E). A sample of 969 graduates of Environmental Education from 1997-2021, were the respondents. The researchers used an open and closed ended questionnaire with a modified four-point Likert scale response options that they designed as an instrument to collect information. Simple percentages were used for data analysis. The results of the analyses show that the curriculum content of Environmental Education as in force today is not adequate. The knowledge and awareness acquired when they studied E.E. did not help them enough to solve their community environmental problems. However, Environmental Education built their skills and prepared them well to actively participate in solving current environmental problems. Some of the lecturers who taught these respondents at undergraduate levels have the requisite pedagogic knowledge of the subject matter but, the government who is a signatory to the implementation of Environmental Education is not serious about engaging these graduates. Overall, Thirteen problems were identified as factors hampering the effective implementation of Environmental Education curriculum, and 13 feasible solutions were proffered by the respondents. It was concluded that Environmental Education in the University of Calabar has achieved some level of success, despite the fact that there are some issues that needs to be addressed to get the complete success anticipated by the crafter of the program’s objectives. It was recommended among others that a regulatory body should be created to regulate the practice of Environmental Education in Nigeria.